2011
DOI: 10.1088/0960-1317/21/7/075015
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced sensitivity of a surface acoustic wave gyroscope using a progressive wave

Abstract: A surface acoustic wave (SAW)-based gyroscope with an 80 MHz central frequency was developed on two different piezoelectric substrates (128° YX LiNbO3 and ST-X quartz). A sensor was developed that contained two SAW oscillators. One oscillator was used as the sensing element and had metallic dots in the cavity between the input and output interdigital transducers (IDTs). The other oscillator was used as a reference element. Two oscillators were formed to extract the Coriolis effect by comparing the oscillation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
19
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 15 publications
2
19
0
1
Order By: Relevance
“…Another type of SAW gyroscope using progressive waves was proposed by Oh et al [16,17]. Figure 9 shows the schematics and the mechanism of a SAW gyroscope based on a progressive wave which consists of a vibrating mass, an absorber, and a two-SAW delay line; one is used as a sensing element and contains a vibrating mass in a cavity, while the other is used as a reference element.…”
Section: Saw Gyroscope Based On Progressive Wavementioning
confidence: 99%
See 1 more Smart Citation
“…Another type of SAW gyroscope using progressive waves was proposed by Oh et al [16,17]. Figure 9 shows the schematics and the mechanism of a SAW gyroscope based on a progressive wave which consists of a vibrating mass, an absorber, and a two-SAW delay line; one is used as a sensing element and contains a vibrating mass in a cavity, while the other is used as a reference element.…”
Section: Saw Gyroscope Based On Progressive Wavementioning
confidence: 99%
“…Moreover, Lee et al [15] and Wang et al [18] have attempted to improve the gyroscope sensitivity by using a differential scheme based on opposing wave propagation directions. Oh et al [16,17] constructed a SAW gyroscope using a progressive wave with different masses and positions for the metallic dot array on an experimental basis. In particular, Wang et al [18] successfully demonstrated a wireless and passive SAW gyroscope using two reflective delay lines.…”
Section: Saw Gyroscope Based On Progressive Wavementioning
confidence: 99%
“…To achieve a breakthrough in the performance of the SAW-based rate sensor, a creative idea was proposed whereby a metallic dot array strategically deposited on the SAW propagation path of SAW devices was considered to enhance the Coriolos force acting on the propagating SAW [ 9 , 10 , 11 ]. The scheme of the proposed SAW rate sensor incorporating a metallic dot array is depicted in Figure 1 .…”
Section: Introductionmentioning
confidence: 99%
“…Obviously, the enhanced Coriolis force will improve significantly the detection sensitivity. Exciting detection sensitivity results (16.7 Hz·deg − 1 ·s − 1 ) were achieved with a 80 MHz rate sensor on X-112°Y LiTaO 3 with a 900 nm Cu dot array distribution [ 9 ]. This provides a good start to break through the detection sensitivity bottleneck of SAW-based rate sensors, even though there is still a great gap between the obtained sensitivity and the demands for real applications.…”
Section: Introductionmentioning
confidence: 99%
“…Перспективным направлением является использование микрогироскопов (МГ) на поверхностных акустических волнах (ПАВ), в основе которых лежит молекулярная кинетика твердого тела [3][4][5][6][7][8][9][10][11][12][13]. На сегодняшний день та-кие датчики активно разрабатываются как в России, так и за рубежом.…”
unclassified